The Nature of Property Rights in Haiti: Mode of Land Acquisition, Gender, and Investment. Issue 3 (3rd July 2019) - Kelly, Liam D.; Deaton, B. James; Amegashie, J. Atsu
Abstract: In Haiti, two primary pathways to land ownership are through the purchase of land and through inheritance. In terms of inheritance, intestate law treats daughters and sons equally with respect to real property. Despite the formal law, we find that women are relatively less tenure secure on their inherited land than men. In contrast, men and women share similar perceptions of tenure security on purchased land. These differences become manifest in conservation investment activities: tree planting, fallowing, and terracing. We find evidence that these activities are less likely to occur by female respondents on their inherited land.